Strategi Pemasaran Pupuk Organik Cair Secara Digital sebagai Solusi untuk Mengatasi SDGs Point 8 di Desa Jati, Kecamatan Sidoarjo, Kabupaten Sidoarjo - Tukiman Tukiman; Luqmanul Hakim; Ramiza Firyal Tuffahati; Nur Annisa; Amelia Dwi Lestari; Salwa Zakiah; Moch. Raffi Eka Putra Joya; Salsabila Arifa; Isna Vasanti; Renhart Christian Damaz; Nur Amirotul Suroyah (Lembaga Pengembangan Kinerja Dosen, 2024)
Jati Village has a unique potential in processing organic waste into Liquid Organic Fertilizer (POC). The waste processing is an effort to preserve the environment and also provide added economic value to the local community. However, in making sales, the community in Jati Village has not implemented the right marketing strategy. Digital marketing offers various tools and platforms that can be used to promote POC. Digital marketing strategies that can be applied include the use of social media such as Instagram, Facebook, Tiktok and Youtube to promote POC through interesting and educational visual content, as well as direct interaction with consumers. By implementing digital marketing strategies, Jati Village can increase the visibility of their POC products, expand their customer base, and increase revenue. This can support the SDGs program, especially point 8, namely Equitable Village Economic Growth. Utilizing technology for marketing can help POC sales sell evenly.